The Smart Internet Current Research and Future Applications - Chignell, Mark; Cordy, James; Ng, Joanna; Yesha, Yelena (Information Systems and Applications, incl. Internet/Web, and HCI, 2010)
I love the idea of a Smart Internet that lets users improve many parts of their lives, pulling together data and services from around the internet. This won't happen with large unwieldy programming requirements. . . it will happen because we're moving towards integrated, simple tasks that users can do on an every day basis. With services available on the cloud, with analytics available, with data that has meaning to the user and not just to some protocol parser - with all of these, users at all levels will be able to do a better job. The users may be small and large enterprises, local governments, individuals, etc. All of this means that as the world is becoming more intelligent, instrumented and more interconnected, we'll be headed towards smarter health care, smarter cities, and smarter lives. " - Gennaro A. Cuomo, IBM Software Group Vice President and IBM Fellow, WebSphere Chief Technology O?cer Congratulations to the team on the publication of this ?rst volume of the IBM CASResearchbookseries!Thisisasigni?cantmilestoneforIBMCASResearch. This series not only captures the innovations resulting from the collaboration acrossIBM technical leaders,IBM CAS faculty members, as well as our network of distinguished academic partners, it also lays the foundation for ongoing c- mercialization of future research initiatives.